Harnessing the Potential of the Blue Economy in Central Java: Mapping, Strategic Development, and Macroeconomic Analysis - Ajeng Pangestika, Almira; Wahyudi, Dwi; Al Farizal Pulungan, Ridson (Politeknik Statistika STIS, 2025)
This study pioneers the mapping and analysis of the blue economy's potential across the 35 regencies/municipalities of Central Java by constructing a novel Blue Economy Index (BEI). Notably, this research is among the first in Indonesia to build the BEI using granular satellite data and digital sensor information, and to apply the Two-Step System GMM approach to dynamically analyze the factors influencing its development. This combination provides unprecedented sub national detail and robust insights into effective policy levers. The findings reveal significant disparities among the southern coastal, northern coastal, and non-coastal areas. The southern coastal regions exhibit higher BEI values compared to their northern coastal and non-coastal counterparts, which fall below the average. Results from the Two-Step System GMM regression analysis indicate that internet usage, infrastructure, and the COVID-19 period exert significant effects on the BEI. Specifically, infrastructure development, proxied by Nighttime Light (NTL), demonstrates a negative impact on the BEI, suggesting that environmentally unsustainable infrastructure may undermine the sustainability of the blue economy. Meanwhile, access to digital technology through internet usage plays a crucial role in fostering inclusive blue economy growth. Based on these findings, the proposed policy recommendations include optimizing environmentally friendly infrastructure development, leveraging digital technology to expand market access, and strengthening the resilience of the blue economy through Adaptive-Responsive-Innovative (ARI) crisis policies. Consequently, the development of the blue economy in Central Java is expected to enhance the sustainable welfare of coastal communities while fully optimizing the potential of coastal areas.